(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Enneagram, is a tool that delves into motivations, needs, desires along with qualms, and has gained prominence for self-discovery. This research paper examines the increasing popularity of the Enneagram in the field of career development, particularly among B-school students in Mumbai. By utilizing the Enneagram, students can increase their acumens for authentic career aspirations, comprehend the strengths and weaknesses, and enhance their communication and work styles. This study emphases on comprehending personality types among B-school students, aiming to guide their career decision-making process. To achieve this, participating students are provided with access to a structured questionnaire with scaled responses. By investigating the correlation between personality types and choices regarding career decision-making process, this research seeks to assist students in achieving clarity while selecting their professional paths based on their unique personalities.